PENGARUH TRANSAKSI PIHAK BERELASI TERHADAP MANAJEMEN LABA DENGAN DEWAN KOMISARIS SEBAGAI MODERASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-2024 - Aditiya Rizqi Febriansah; Siti Mutmainah (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of related party transactions on earnings management with board of commissioners characteristics as moderating variables in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. The characteristics of the board of commissioners are proxied by independent commissioners and board size. This study employs agency theory as the underlying theoretical framework. The sample was selected using a purposive sampling method, resulting in 179 observations. The analytical method used in this study was panel data regression analysis with the Common Effect Model and moderated regression analysis. The results indicate that related party transactions have a significant negative effect on earnings management. Independent commissioners are not proven to moderate the effect of related party transactions on earnings management. Meanwhile, board size is proven to moderate the effect of related party transactions on earnings management with a negative direction, indicating that board size weakens the positive effect of related party transactions on earnings management. These findings suggest that the monitoring capacity of the board of commissioners plays an important role in limiting the potential use of related party transactions in earnings management practices.